Understanding the truly value creating resources – the case of a pharmaceutical company. (12th May 2004) - Fernstrom, Lisa; Pike, Stephen; Roos, Goran
All companies benefit from better understanding and managing their intangible assets. This is especially true for research-intensive enterprises dependent on non-physical resources and is why we have chosen to use the case of the R&D department of a pharmaceutical company to illustrate how to visualise the true value creating resources in an organisation. Using the resource-based view and the intellectual capital perspective, we discuss a powerful methodology for mapping both the tangible and the intangible resources of the firm and their interaction with one another. The methodology extends to assessing the effectiveness with which the resources are deployed as well as the robustness of the resources (according to criteria of adequacy, volatility, quality, usability and versatility), providing a foundation for competitive advantage. The case of the pharmaceutical company shows how the IC perspective helped enhance the long-term strategic focus of the R&D department and its shorter-term operational capability.